A Pilot Experiment to Replace Missing Rainfall Events Using Soil Moisture Information from the Kansas Mesonet - N. Parker; A. Patrignani (Kansas Agricultural Experiment Station Research Reports, 2020)
The Kansas Mesonet is a state-of-the-art environmental monitoring network that provides accurate rainfall measurements across Kansas. However, missing rainfall records are common problems in weather stations that rely on tipping bucket rain gauges. In this study, we conducted a pilot experiment to estimate missing rainfall records from root-zone soil moisture information recorded at Kansas Mesonet stations. Soil moisture is recorded at depths of 5, 10, 20, and 50 cm using the Campbell Scientific CS655 soil water reflectometer. Hourly rainfall and soil moisture data from mid- August 2017 to mid-May 2018 were taken from three stations (Lakin, Manhattan, and Hays) of the Kansas Mesonet. Rainfall was estimated as the difference in soil moisture storage between 1 hour before and 1 hour after a given rainfall event. Preliminary results show that soil moisture-derived rainfall can be more accurate than using rainfall data from nearby stations. Soil moisture could serve as very useful information in quality control procedures to flag missing rainfall events.
Keywords: soil moisture; Kansas Mesonet; precipitation